Full-length transcriptome analysis reveals the mechanism of acupuncture at PC6 improves cardiac function in myocardial ischemia model - Jing Yuan; Jun-Meng Wang; Zhi-Wei Li; Cheng-Shun Zhang; Bin Cheng; Su-Hao Yang; Bai-Tong Liu; Li-Juan Zhu; Ding-Jun Cai; Shu-Guang Yu (BMC, 2021)
Abstract Background The pathological process of myocardial ischemia (MI) is very complicated. Acupuncture at PC6 has been proved to be effective against MI injury, but the mechanism remains unclear. This study investigated the mechanism that underlies the effect of acupuncture on MI through full-length transcriptome. Methods Adult male C57/BL6 mice were randomly divided into control, MI, and PC6 groups. Mice in MI and PC6 group generated MI model by ligating the left anterior descending (LAD) coronary artery. The samples were collected 5 days after acupuncture treatment. Results The results showed that treatment by acupuncture improved cardiac function, decreased myocardial infraction area, and reduced the levels of cTnT and cTnI. Based on full-length transcriptome sequencing, 5083 differential expression genes (DEGs) and 324 DEGs were identified in the MI group and PC6 group, respectively. These genes regulated by acupuncture were mainly enriched in the inflammatory response pathway. Alternative splicing (AS) is a post-transcriptional action that contributes to the diversity of protein. In all samples, 8237 AS events associated with 1994 genes were found. Some differential AS-involved genes were enriched in the pathway related to heart disease. We also identified 602 new genes, 4 of which may the novel targets of acupuncture in MI. Conclusions Our findings suggest that the effect of acupuncture on MI may be based on the multi-level regulation of the transcriptome.